Long-term warming results in species-specific shifts in seed mass in alpine communities - Zhang, Chunhui; Ma, Zhen; Zhou, Huakun; Zhao, Xinquan (PeerJ, 2019)
Background Global warming can cause variation in plant functional traits due to phenotypic plasticity or rapid microevolutionary change. Seed mass represents a fundamental axis of trait variation in plants, from an individual to a community scale. Here, we hypothesize that long-term warming can shift the mean seed mass of species. Methods We tested our hypothesis in plots that had been warmed over 18 years in alpine meadow communities with a history of light grazing (LG) and heavy grazing (HG) on the Qinghai-Tibet plateau. In this study, seeds were collected during the growing season of 2015. Results We found that warming increased the mean seed mass of 4 (n = 19) species in the LG meadow and 6 (n = 20) species in the HG meadow, while decreasing the mean seed mass of 6 species in the LG and HG meadows, respectively. For 7 species, grazing history modified the effect of warming on seed mass. Therefore, we concluded that long-term warming can shift the mean seed mass at the species level. However, the direction of this variation is species-specific. Our study suggests that mean seed mass of alpine plant species appears to decrease in warmer (less stressful) habitats based on life-history theory, but it also suggests there may be an underlying trade-off in which mean seed mass may increase due to greater thermal energy inputs into seed development. Furthermore, the physical and biotic environment modulating this trade-off result in complex patterns of variation in mean seed mass of alpine plant species facing global warming.
Keywords: Climate change; Functional traits; Grazing; Qinghai-tibet plateau; Trait variation